Pengembangan Media Pembelajaran Menulis Teks Persuasi Berbasis Canva - Ganeswara, Muhamad Ginanjar; Atih*, Atih (Universitas Suryakanca, 2025)
This article will present the results of the development of Indonesian language learning media in SMPN based on Canva. The study used the Research and Development (R&D) method with the ADDIE model, including analysis, design, development, implementation and evaluation. Validation was carried out by language experts (100%), material experts (100%) and media experts (90%). The responses of educators (91.5%) and students (96.41%) were also very valid. Thus, it can be concluded that Canva-based learning media in the Indonesian language subject of persuasive text material for class VIII is suitable for use as a learning medium..Keywords: Canva; learning media; persuasive textAbstrakArtikel ini akan memaparkan hasil pengembangan media pembelajaran bahasa Indonesia di SMPN berbasis Canva. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE, mencakup analisis, rancangan, pengembangan, penerapan dan evaluasi. Validasi dilakukan oleh ahli bahasa (100%), ahli materi (100%) dan ahli media (90%). Respon pendidik (91,5%) dan peserta didik (96,41%) juga sangat valid. Dengan demikian dapat disimpulkan bahwa media pembelajaran berbasis Canva pada mata pelajaran bahasa Indonesia materi teks persuasi kelas VIII layak digunakan sebagai media pembelajaran. Katakunci: Canva; media pembelajaran; teks persuasi